Pananahimik, Pamumuná, Pagtutol, at Pag-asa: Isang Pagdalumat sa Praktis ng Sci-Hub. - Cortez, Franz Giuseppe F. (KRITIKE: An Online Journal of Philosophy, 2022)
In this study, I explore the practice of Sci-Hub using some concepts derived from the Brazilian philosopher Paulo Freire and the Canadian philosopher Henry Giroux. These are the concepts of culture of silence, language of critique, culture of resistance and language of hope. In general, the world of education silently and passively accepts a regime perpetrated by giant publishing corporations. The practice of Sci-Hub mirrors a critique of a form of oppression and domination of consciousness - that a sensible rationality, discourse, and regime is one which is advocated by big corporations. I affirm that Sci-Hub is a creative response to a culture of silence effectively perpetuated by the regime of intellectual property, publishing industry and corporatization of the school. But at the same time, the practice of Sci-Hub manifests a clinging to the language of hope that resists the ideology of "There Is No Alternative" (TINA). Despite the inherent difficulties in the contemporary society, the practice of Sci Hub persists to look for small spaces to offer effective alternatives to the present order or lack of it.